2011
DOI: 10.1097/mol.0b013e3283412279
|View full text |Cite
|
Sign up to set email alerts
|

Possible contributions of lipoproteins and cholesterol to the pathogenesis of diabetes mellitus type 2

Abstract: LDL, HDL and cholesterol regulate the function and survival of β-cells. HDL also exerts antiobesity and insulin-sensitizing effects. Thus dyslipidemias may not only be consequences but also contributors to the pathogenesis and hence targets for prevention of T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 51 publications
1
105
0
1
Order By: Relevance
“…Since it has been suspected that LDLR mediated lipotoxicity can alter beta cell function [6], a potential safety issue with the use of PCSK9 inhibitors is the increased risk of type 2 diabetes. However, results obtained from Pcsk9-deficient mice are discordant.…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been suspected that LDLR mediated lipotoxicity can alter beta cell function [6], a potential safety issue with the use of PCSK9 inhibitors is the increased risk of type 2 diabetes. However, results obtained from Pcsk9-deficient mice are discordant.…”
Section: Introductionmentioning
confidence: 99%
“…Altered intracellular cholesterol homeostasis and impaired insulin secretion were observed in mice with beta-cell dysfunction for ABCA1 15 . Subjects carrying loss-of-function mutations in ABCA1 show impaired insulin secretion but not insulin resistance 34,35 . In our present study, a significant association was identified between polymorphisms within ABCA1 SNP 22 found that the ABCA1 R230C variant is associated with early-onset T2DM in the Mexican population.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with low HDL cholesterol are often insulin resistant and at increased risk of developing T2DM (Li et al 2014;von Eckardstein and Sibler 2011). T2DM, the metabolic syndrome, and IR are characterized by hyperinsulinemia and increased free fatty acids (FFA).…”
Section: Low Hdl Cholesterol Levels In Diabetes and Metabolic Syndromementioning
confidence: 99%
“…Traditionally, a reduced plasmatic level of HDL cholesterol has been interpreted to be the result of such metabolic perturbations, which are already present in the prediabetic state, and hence an innocent bystander of T2DM. However, several more recent studies suggest that HDLs help to maintain euglycemia via both insulin-dependent and insulin-independent pathways (Drew et al 2012;von Eckardstein and Sibler 2011). The infusion of artificially reconstituted HDL (rHDL) was found to improve glycemia in patients with T2DM (Drew et al 2009).…”
Section: Hdl Metabolism Subclasses and Catabolismmentioning
confidence: 99%
See 1 more Smart Citation